Middle distance : a graphic memoir - Choy, Mylo (SelfMadeHero, 2023)
"A charming, heartwarming, and poignant story of running and self-acceptance, Mylo Choy's Middle Distance combines exertion and introspection in an exploration of the physical body's connection to the human experience. An exciting graphic addition to a growing field, this sports memoir recounts Mylo's history with running, and how their love for that famously solitary sport pushed them to grow over time. As Middle Distance grapples with themes of resilience, identity, and self-care, Mylo leads us along the middle way between motion and rest, hurt and healing, fear and joy. The result is an honest, nuanced work of subtle power that will appeal to all runners, especially those who are transgender or nonbinary."--Amazon.com.